2010
DOI: 10.1021/nn102272n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Biologically Active Silver from Nanosilver Surfaces

Abstract: Major pathways in the antibacterial activity and eukaryotic toxicity of nano-silver involve the silver cation and its soluble complexes, which are well established thiol toxicants. Through these pathways, nano-silver behaves in analogy to a drug delivery system, in which the particle contains a concentrated inventory of an active species, the ion, which is transported to and released near biological target sites. Although the importance of silver ion in the biological response to nano-silver is widely recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
823
7
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(885 citation statements)
references
References 56 publications
37
823
7
11
Order By: Relevance
“…This finding suggests a dominant effect of SA in determining Ag loss and confirms findings by other studies. 34 The permutation in the order of maximum Ag release as compared to the expected order (smaller particles release more) suggests that other unidentified factors could also play a role.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This finding suggests a dominant effect of SA in determining Ag loss and confirms findings by other studies. 34 The permutation in the order of maximum Ag release as compared to the expected order (smaller particles release more) suggests that other unidentified factors could also play a role.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…For similar reasons, aggregated NPs expose less surface to the solvent than separated NPs, and thus possess a lower antibacterial impact [64]. While size of the NPs is a crucial parameter to determine their proper activity per unit of mass (or mole), it has been recently demonstrated by Liu et al [65] that the released Ag + scaled well if the sample were normalized by their exposed surface. Afterwards, Xiu et al [21] showed in 2012 that the significant parameters to evaluate the activity of silver nanoparticles were the silver released as Ag + and not the amount of elemental silver introduced as nanoparticle (Fig.…”
Section: Role Of Ag + Speciesmentioning
confidence: 99%
“…(ii) The second lever of control consists in improving the availability of the silver antibacterial species, by tuning the dissolution of the NPs. This aspect involves a control of the Ag NPs size, shape and coating [65]. It is also preferable to avoid surface passivation, formation of insoluble precipitates or aggregation of the NPs.…”
Section: Factors Involved In the Control Of The Activitymentioning
confidence: 99%
“…The zeta potential of nAg‐sorbitol (−28.2 ± 2.1 mV) was lower than that of nAg (−22.1 ± 1.5 mV) in a neutral environment (Figure 6b). The decrease in zeta potential suggested an increase in electronegative groups,35 that is, the coating of hydroxyls from d ‐sorbitol. In contrast, the presence of H + shielded the electronegativity of the hydroxyls, as shown by the higher zeta potential in an acid environment (−26.4 ± 0.5 mV) than in a neutral environment (−28.2 ± 2.1 mV).…”
Section: Resultsmentioning
confidence: 99%